Long-term effect of exposure to ambient air pollution on the risk of active tuberculosis. (October 2019) - Li, Zhongqi; Mao, Xuhua; Liu, Qiao; Song, Huan; Ji, Ye; Xu, Dian; Qiu, Beibei; Tian, Dan; Wang, Jianming
Highlights: Exposure to ambient PM2.5, PM10, SO2, and NO2 contributes to an increased risk of active tuberculosis. The effect of ambient air PM10 and NO2 in the risk of tuberculosis remains significant in the multi-pollutant models. This is the first DLNM-based time-series study exploring the long-term effect of ambient air pollution on the risk of tuberculosis. Reducing the concentration of ambient air pollutants is likely to bring about health benefits in tuberculosis-endemic areas. Abstract: Objectives: To explore the long-term effect of exposure to ambient air pollution on the risk of active tuberculosis (TB). Methods: We constructed a distributed-lag nonlinear model (DLNM) to evaluate the relatively long-term influence of outdoor PM2.5, PM10, SO2 and NO2 exposure on active TB risk in the city of Lianyungang in Jiangsu Province, China. Results: There were 7, 282 TB cases reported in the study area during 2014–2017, with annual median (interquartile range) concentrations of PM2.5, PM10, SO2 and NO2 at 45.86 (34.57–64.14) μg/m 3, 85.43 (62.86–116.14) μg/m 3, 22.00 (15.71–30.86) μg/m 3 and 30.00 (23.29–38.57) μg/m 3, respectively. The single-pollutant model showed that for each 10 μg/m 3 increase in concentration, the cumulative relative risk of TB was 1.12 (lag 0–24 weeks, 95% CI: 1.03–1.22) for PM2.5 with reference to 35 μg/m 3 ; 1.11 (lag 0–21 weeks, 95% CI: 1.06–1.17) for PM10 with reference to 70 μg/m 3 ; 1.37 (lag 0–20 weeks, 95% CI: 1.16–1.62) for SO2 with reference to 60 μg/m 3 ; and 1.29 (lag 0–22 weeks, 95% CI: 1.11–1.49) for NO2 with reference to 40 μg/m 3 . In the multipollutant model considering both PM10 and NO2, the association remained significant. Conclusions: Our results revealed a potential association between outdoor exposure to PM2.5, PM10, SO2, and NO2 and active TB. Considering that people from developing countries continue to be exposed to both severe outdoor air pollution and high rates of latent TB infection, the association between worsening air pollution and active TB deserves further attention.